PENGEMBANGAN VIRTUAL TOUR 3D GEDUNG UNIVERSITAS AMIKOM PURWOKERTO SEBAGAI MEDIA INTERAKTIF PENGENALAN KAMPUS: DEVELOPMENT OF A 3D VIRTUAL TOUR OF UNIVERSITAS AMIKOM PURWOKERTO BUILDINGS AS AN INTERACTIVE CAMPUS INTRODUCTION MEDIUM - Manggala Yuda al Harits; Zulia Karini; Ely Purnawati (LPPM Universitas Abdurrab, 2026)
Competition among higher education institutions in attracting prospective students has increased the need for more innovative and interactive campus introduction media. Conventional media such as brochures and static photographs are considered less effective in providing comprehensive spatial information about the campus environment. This study aims to develop a three-dimensional virtual tour of Universitas Amikom Purwokerto buildings using the Roblox platform as an interactive, engaging, and easily accessible campus introduction medium. The development process employed the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The 3D modeling of campus buildings was created using Blender software and integrated into the Roblox platform through Roblox Studio to produce an interactive virtual environment. Functional testing results indicated that all main system features operated properly, including character navigation, interactive information panels, and accessibility on both PC and mobile devices. User evaluation was conducted through a beta testing session involving 30 respondents using a five-point Likert scale questionnaire. The evaluation results showed that the average score of all indicators ranged from 4.37 to 4.77, with the highest scores obtained for the intention to recommend the media to others (4.77) and its effectiveness compared to conventional media (4.70). These findings demonstrate that the Roblox-based 3D virtual tour is an effective, informative, interactive, and easily accessible medium for introducing the campus environment to prospective users.